Biodiesel Production From Oleic Acid Using Biomass-Derived Sulfonated Orange Peel Catalyst - Kumawat, Manoj Kumar; Rokhum, Samuel Lalthazuala (Frontiers in Catalysis, 2022)
Biodiesel, as an alternative fuel for petroleum-based fuel, has recently acquired significant attention. The current study focused on using biowaste to produce catalysts for low-cost biodiesel manufacturing. Orange peels (OP) were used to make carbon-based solid acid catalysts with sulfonic acid group (–SO3H) density of 1.96 mmol g-1 via a ‘one-pot’ carbonization-sulfonation treatment. Under the optimized reaction conditions (15:1 MeOH to oleic acid molar ratio, 7 wt. % catalyst loading w.r.t oleic acid, 80 °C reaction temperature, 60 mins reaction time), 96.51±0.4 % conversion of oleic acid to methyl oleate (a biodiesel component) was obtained. The catalyst displayed high recyclability and stability on repeated reuse, with a negligible decrease in biodiesel conversion up to 5 catalytic cycles.